2019
DOI: 10.1002/app.48155
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline‐loaded pectin‐based hydrogels. II. Effect of concentration of initial pectin solution, crosslinker type and cation concentration of external solution on drug release profile

Abstract: A series of drug-loaded pectin hydrogels were prepared by mixing method in two ion types, Ca +2 or Zn +2 , for wound dressing applications and their drug release performances were investigated at pH 6.4 in four different calcium ion concentrations of external solution. Pectin hydrogels were synthesized in three different concentrations of initial pectin solution and theophylline was used as a model drug. Fourier transform infrared spectroscopy, scanning electron microscopy, and atomic force microscopy were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Particularly, Zn 2+ ions are used as an alternative cross-linker because they produce a stronger pectinate network and show improved stability in the upper gastro-intestinal tract [ 8 ]. Zinc ions are added to biomaterials, especially for wound healing, due to their antibacterial action [ 9 ]. Transition metal ions such as Fe 3+ ions are used as an alternative to Ca 2+ cross-linkers to produce a pectinate network [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, Zn 2+ ions are used as an alternative cross-linker because they produce a stronger pectinate network and show improved stability in the upper gastro-intestinal tract [ 8 ]. Zinc ions are added to biomaterials, especially for wound healing, due to their antibacterial action [ 9 ]. Transition metal ions such as Fe 3+ ions are used as an alternative to Ca 2+ cross-linkers to produce a pectinate network [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers reported the superiority of Zn 2+ over Ca 2+ in showing improved stability in the upper gastro-intestinal tract and slower drug release [ 8 ]. In the study by Sarioglu E. et al [ 9 ], zinc-containing hydrogel for wound dressing showed better controlled drug release behavior and antibacterial activity than Ca 2+ -cross-linked hydrogel. It was shown that zinc and calcium interact with pectin chains differently.…”
Section: Introductionmentioning
confidence: 99%
“…The wettability of dry films with BSA is determined by measuring the contact angles using direct image analysis of sessile drops (Figure 9). While the water contact angle (WCA) of pectin hydrogel film without zeolite is 55 • [27], this value shifts to 77 • and 100 • with the addition of zeolite and BSA to the hydrogel, respectively. Results are in agreement with zeta potential measurements.…”
Section: Water Contact Angle Measurementsmentioning
confidence: 99%
“…Due to their anionic character, pH-sensitive pectin hydrogel films appear as good candidates for controlled release systems to treat wounds, where pH changes according to the healing progress. We recently showed the controlled drug delivery ability of pectin-based hydrogels [26][27][28][29], where the mechanical and thermal properties can be adjusted with the addition of other polymeric or inorganic materials [25,29,30]. These hydrogels combined a variety of properties desired for a wound dressing, where high oxygen permeability, moisture-holding capacity, and antimicrobial properties are a few from the long list.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium ions are mainly used as a cross-linker to obtain ionotropic LM pectin hydrogels. Other divalent (Zn 2+ , Mg 2+ ) [ 14 , 15 , 16 , 17 ] and trivalent (Fe 3+ , Al 3+ ) [ 18 , 19 , 20 , 21 ] cations are increasingly being considered as an alternative to calcium ions in order to improve the physicochemical and functional properties of calcium pectin hydrogels. However, the effect of the cross-linking cation on the adhesiveness of the pectin hydrogel to the serosa has not been studied before.…”
Section: Introductionmentioning
confidence: 99%